Walter Stewart correspondence and regimental lists - Stewart, Walter, 1756-1796.
Correspondence concerning events of the Revolutionary War; regimental lists drawn up by Stewart as inspector for the Northern Army; and later business correspondence. Correspondents include Henry Jackson and John Nicholson.
Continental Army officer and merchant of Philadelphia, Pa.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Jackson, Henry, -- 1747-1809 -- Correspondence; Nicholson, John, -- 1757-1800 -- Correspondence; United States. -- Continental Army -- Inspection; Merchants -- Pennsylvania -- Philadelphia; United States -- History -- Revolution, 1775-1783.; Army officers; Merchants